Probing the relationship between ecosystem perceptions and approaches to environmental governance: an exploratory content analysis of seven water dilemmas. Issue 1 (2nd January 2018) - Plummer, Ryan; Baird, Julia; Bullock, Ryan; Dupont, Diane; Renzetti, Steven
Abstract: Addressing wicked 'water dilemmas' requires an understanding of the context within which they are embedded. This study explored perceptions of the ecosystem in terms of resilience and the governance approaches employed through a content analysis of documents from seven case studies across the globe. Analytical constructs developed for resilience and governance approaches guided the exploration. Multiple resilience types were present in documents for each case, but few patterns emerged across cases. Governance approaches were strongly focused on state approaches in most cases. A relationship between resilience type and governance approach was not clear; however, a pattern emerged between the presence of the social–ecological resilience type and non-state-centred governance forms. The type of author (government, non-government) or the type of document (research and advisory, descriptive) were not found to mediate the findings as resilience framings varied considerably and state governance approaches were emphasised throughout. As the findings stand in contrast to contemporary scholarship on understanding ecosystems and environmental governance they raise important issues to which individuals must be cognizant when accessing documents for guidance. They also open avenues for future investigation of water dilemmas at the nexus of theory, policy and practice.